The effects of dietary energy density and lysine:calorie ratio on the growth performance of the 20 to 55 lb pig - J W Smith II; W B Nessmith Jr; J R Bergstrom; K Hongtrakul; J A Loughmiller; R E Musser; Michael D Tokach; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1996)
A total of 336 barrows (initially 21.8 lb and 31 ± 2 d of age) was used to evaluate the results of increasing levels of choice white grease and lysine:calorie ratio on pig performance. Increasing levels of both choice white grease and lysine:calorie ratio improved the growth rate and efficiency of pigs fed from 20 to 55 lb.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Energy density; Lysine:calorie ratio; Performance